On the Cable Pseudo-Drag Problem of Cable-Driven Parallel Camera Robots at High Speeds. Issue 10 (4th March 2019) - Wei, Huiling; Qiu, Yuanying; Sheng, Ying
Summary: This paper presents a control strategy for solving the cable pseudo-drag problem of cable-driven parallel camera robots at high speeds. The control strategy belongs to a hybrid position/tension control method based on cable tension optimization. The cable catenary model and cable pseudo-drag problem are considered firstly. Then, the dynamic model of the cable-driven parallel camera robot is established. The cable tension optimization is proposed. And then a control strategy is put forward and its stability is proved. Simulation results of a four-cable camera robot are presented and discussed.